Modulation of glacier ablation by tephra coverage from Eyjafjallajökull and Grímsvötn volcanoes, Iceland: an automated field experiment - Möller, Rebecca; Möller, Marco; Kukla, Peter A.; Schneider, Christoph (RWTH Aachen University, 2018)
Earth system science data : ESSD 10(1), 53-60 (2018). doi:10.5194/essd-10-53-2018 : Published by Copernics Publications, Katlenburg-Lindau